2001
DOI: 10.1029/1999ja000451
|View full text |Cite
|
Sign up to set email alerts
|

Plasmoid ejection and auroral brightenings

Abstract: Abstract. Geotail plasma and magnetic field observations of 24 plasmoids between 21 and 29 R• have been compared with Polar ultraviolet observations of auroral brightenings. Both single and multiple plasmoids almost always corresponded to brightenings, but the brightenings were sometimes weak and spatially limited and did not always grow to a global substorm. Even a case where a plasmoid event occurred with fast postplasmoid flow corresponded to a weak brightening but no substorm. Some brightenings did not cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
107
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 29 publications
10
107
1
Order By: Relevance
“…Not only was a close temporal-spatial relationship found for auroras and isolated BBF events (including both tailward flow bursts corresponding to the plasmoids, Ieda et al, 2001 and earthward flows near the center of an expanded plasma sheet, Nakamura et al, 2001a, b), but the absence of perpendicular (cross-B) plasma flows in the plasma sheet in the absence of the auroral activations was also shown (Ieda et al, 2003). This close relationship suggests the attractive possibility of using the auroral activations as a tool for monitoring the high-speed plasma sheet flows if their spatial relationship and the mechanism generating the precipitation can be established.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Not only was a close temporal-spatial relationship found for auroras and isolated BBF events (including both tailward flow bursts corresponding to the plasmoids, Ieda et al, 2001 and earthward flows near the center of an expanded plasma sheet, Nakamura et al, 2001a, b), but the absence of perpendicular (cross-B) plasma flows in the plasma sheet in the absence of the auroral activations was also shown (Ieda et al, 2003). This close relationship suggests the attractive possibility of using the auroral activations as a tool for monitoring the high-speed plasma sheet flows if their spatial relationship and the mechanism generating the precipitation can be established.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, a close relationship between the fast bursty plasma sheet flows (BBFs) and auroral activations was confirmed observationally for a wide range of activity and for different types of transient auroral structures, including the localized auroral brightenings and pseudobreakups, and north-south auroras (or auroral streamers) (Fairfield et al, 1999;Ieda et al, 2001;Nakamura et al, 2001b;Sergeev et al, , 2001Lyons et al, 1999). Not only was a close temporal-spatial relationship found for auroras and isolated BBF events (including both tailward flow bursts corresponding to the plasmoids, Ieda et al, 2001 and earthward flows near the center of an expanded plasma sheet, Nakamura et al, 2001a, b), but the absence of perpendicular (cross-B) plasma flows in the plasma sheet in the absence of the auroral activations was also shown (Ieda et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…The time relationship between plasmoids and auroral pseudo-breakups was studied by Ieda et al (2001). They found that the earliest plasmoid was observed at X=−28 R E about 2 min before the auroral brightening.…”
Section: ∼5mentioning
confidence: 99%
“…Runov et al: Tailward flows in the near-Earth magnetotail Plasmoid-related tailward flows were found to be almost always associated with auroral breakups or pseudo-breakups (Ieda et al, 2001;Nakamura et al, 2001).…”
mentioning
confidence: 99%
“…The lobe reconnection X-line substantially evolved tailward. Ieda et al (2001) studied brightenings in the polar ionosphere when plasmoids were observed in midtail. They found that the brightenings are closely related with the formation of plasmoids.…”
Section: Discussionmentioning
confidence: 99%